2001
DOI: 10.1051/0004-6361:20010820
|View full text |Cite
|
Sign up to set email alerts
|

A BeppoSAX observation of Her X-1 during the first main-on after an anomalous low-state: Evidence for rapid spin-down

Abstract: Abstract.Results of a BeppoSAX observation of Her X-1 in 2000 October during the first main-on state after the longest recorded anomalous low-state are presented. The 0.1-30 keV spectrum, light curve and pulse profile are all consistent with those measured during previous main on-states, indicating that Her X-1 has resumed its regular 35 day cycle with similar on-state properties as before. However, from a comparison of the measured pulse period with that obtained close to the start of the anomalous low-state,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 21 publications
10
38
1
Order By: Relevance
“…The best-fit value corresponds to a radius of ∼250 km for the blackbody, similar to the values found by Endo et al (2000). This feature is consistently seen in all soft X-ray observations at similar temperatures, kT ≈ 130 eV; see, e.g., Ji et al (2009) and Oosterbroek et al (2001). In the FDcut model, the blackbody temperature kT was not constrained by the fit, so we fixed it to 140 eV, the average value given by the two other models.…”
Section: Soft Componentssupporting
confidence: 84%
“…The best-fit value corresponds to a radius of ∼250 km for the blackbody, similar to the values found by Endo et al (2000). This feature is consistently seen in all soft X-ray observations at similar temperatures, kT ≈ 130 eV; see, e.g., Ji et al (2009) and Oosterbroek et al (2001). In the FDcut model, the blackbody temperature kT was not constrained by the fit, so we fixed it to 140 eV, the average value given by the two other models.…”
Section: Soft Componentssupporting
confidence: 84%
“…The arrow in the figure indicates the epoch of present observations. It is clearly seen from the figure that present data correspond to the main-on due to a delayed onset of the source as noted by Oosterbroek et al (2001). It is also seen from the figure that in the post-anomalous state, the second main-on represents the normal behaviour during which the source intensity remained high for about 10 days, while the first main-on was of much shorter duration.…”
Section: Resultssupporting
confidence: 75%
“…(Parmar et al 1999;Levine & Corbet 1999;Coburn et al 2000). Using BeppoSAX observations during the first main-on after the anomalous low state, Oosterbroek et al (2001) have reported the evidence that the rapid spin down of the source continued during the entire ALS period and the source pulse period changed to the value observed in 1984/5. The measured pulse period of 1237.7697 corresponds to aṖ P ∼ 3 × 10 −6 yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the hard-soft phase shift appears to vary more rapidly for SMC X-1 (a change of Ӎ90Њ between and 0.42) than for f Ӎ 0.16 SO Her X-1 (Ӎ20Њ between and 0.17; Zane et al 2004). f Ӎ 0.03 SO Third, it is not completely clear even in Her X-1 that the phase variation is caused by the 35 day disk precession; soon after the observations of Zane et al (2004), the source entered an anomalous low state, an event that may be caused by changes in the inner disk structure (Boyd & Still 2004;Oosterbroek et al 2001). Such changes could alter the shape of the inner reprocessing region, and thus the soft profiles, in a way that is not directly related to the superorbital period.…”
Section: Timing Analysismentioning
confidence: 99%